Role of serum total sialic acid in differentiating cholangiocarcinoma from hepatocellular carcinoma - Kongtawelert P. (2014)
Aim: This study was designed to evaluate the clinical application of serum total sialic acid (ISA) in the diagnosis of cholangiocarcinoma (CCA). Methods: Serum TSA was determined by periodateresorcinol microassay in 69 patients with CCA, 59 patients with hepatocellular carcinoma (HCC), 37 patients with cirrhosis, 61 patients with chronic hepatitis and 50 healthy blood donors. Results: The mean serum TSA concentration in CCA (2.41±0.70 mmol/L) was significantly higher than those of HCC, cirrhosis, chronic hepatitis and healthy blood donors (1.41±0.37 mmol/L, 1.13±0.31 mmol/L, 1.16±0.26 mmol/L, and 1.10±0.14 mmol/L, respectively; p<0.001). Based on ROC curve analysis, a cut-off point of 1.75 mmol/L discriminated between CCA and HCC with a sensitivity, specificity and accuracy of 82.6 %, 83.1 %, and 82.8 %, respectively. Conclusion: Based on our results, serum TSA would be a useful marker for the differential diagnosis of CCA from HCC.